Joniškio šnektos priebalsinio kamieno daiktavardžių linksniavimas - Kaikarytė, Aušra (Baltistica, 2005)
THE DECLENSION OF CONSONANT STEM NOUNS IN THE SUBDIALECT OF JONIŠKIS The article deals with the declension of consonant stem nouns in one of the nothern West-Aukštaitian subdialects and shows the inner motives of any observed changes. It demonstrates that the consonant stem nouns compose an unstable inflectional class in the subdialect of Joniškis. The consonant stem nouns pass to the stable noun classes by way of the i stem class: the feminine consonant stem nouns get the unmarked inflection from the stable iā̯, ē stem feminine nouns, whereas the masculine consonant stem nouns get their unmarked inflection from the stable masculine (i)i̯ŏ, ŏ stem nouns. Only the consonant stem inflection of the nominative singular and genitive plural cases is maintained much better. The nouns sæ̀suo̾ and vὰnduo̾ still maintain the shortened consonant stem inflection of the genitive singular case.